Economic Case for Scale-up of the WHO Surgical Safety Checklist at the National Level in Sub-Saharan Africa. Issue 5 (15th May 2022) - White, Michelle C.; Leather, Andrew J. M.; Sevdalis, Nick; Healey, Andy
Abstract : Objectives: To evaluate the economic case for nationwide scale-up of the World Health Organization (WHO) Surgical Safety Checklist using cost-effectiveness and benefit-cost analyses. Background: The Checklist improves surgical outcomes but the economic case for widespread use remains uncertain. For perioperative quality improvement interventions to compete successfully against other worthwhile health and nonhealth interventions for limited government resources they must demonstrate cost-effectiveness and positive societal benefit. Methods: Using data from 3 countries, we estimated the benefits as the total years of life lost (YLL) due to postoperative mortality averted over a 3 year period; converted the benefits to dollar equivalent values using estimates of the economic value of an additional year of life expectancy; estimated total implementation costs; and determined incremental cost-effectiveness ratio (ICER) and benefit-cost ratio (BCR). Costs are reported in international dollars using Word Bank purchasing power parity conversion factors at 2016 price-levels. Results: In Benin, Cameroon, and Madagascar ICERs were: 31, 138, and 118 per additional YLL averted; and BCRs were 62, 29, and 9, respectively. Sensitivity analysis demonstrated that the associated mortality reduction and increased usage due to Checklist scale-up would need to deviate approximately 10-fold from published data to change our main interpretations. Conclusions: According to WHO criteria, Checklist scale-up is considered "very cost-effective" and for every 1 spent the potential return on investment is 9 to 62. These results compare favorably with other health and nonhealth interventions and support the economic argument for investing in Checklist scale-up as part of a national strategy for improving surgical outcomes.